The environmental and population health benefits of active transport: a review - Larouche, Richard; Larouche, Richard (Université d'Ottawa | University of Ottawa, 2012)
Since most individuals must travel to work or to school on a daily basis, active transport (e.g. using active modes of transportation such as walking and cycling) is increasingly regarded as a promising alternative to increase physical activity (PA) levels. Furthermore, transport activities account for 23% of CO2 emissions and this proportion is steadily increasing. Therefore, active transport (AT) may represent a promising strategy to address many environmental and public health issues. The current book chapter is organized into four parts. First, the impact of various transportation strategies to reduce emissions of GHG and other pollutants are described. Second, the impacts of AT on physical activity, physical fitness and other health-related outcomes are summarized. Third the correlates of AT are briefly examined to identify key variables to consider for the promotion of AT as a strategy to reduce GHG emissions and increase physical activity. Finally, the fourth section examines the interrelationships between the environmental and public health impacts of AT. Overall, this body of evidence should be useful for policy-makers to justify investments to promote AT by the perspective of combined environmental and public health benefits.